The devil may dance : [large type] a novel - Tapper, Jake (Tapper, Jake. Charlie and Margaret Marder mystery, 2021)
"Charlie and Margaret Marder, political stars in 1960s Washington DC, know all too well how the tangled web of power in the nation's capital can operate. But while they long to settle"--